Ultrastructural Changes in Bovine Oocytes Induced During In Vitro Production of Embryos - Kanwal, Kiron Deep Singh (1999)

(untitled)
Despite substantial progress in the development of procedures for in vitro maturation, in vitro fertilisation and in vitro culture, the production of viable embryos in most laboratories is around 20-30%. The objective of this study was to examine ultrastructural changes induced in bovine oocytes during various stages of in vitro embryo production as these changes could contribute towards the low viability of the embryos. The oocytes recovered from slaughterhouse ovanes were transported in modified Dulbecco's phosphate buffered saline for various periods of time at two different temperatures, in vitro matured (WM), in vitro fertilised (WF) and in vitro cultured (WC) to morulae stages. After submitting to various stages mentioned above the oocytes were processed for transmission electron microscopy and examined in Hitachi 7100 or Phillips CM 12 electron microscopes at 75 or 80 kV respectively. Results exhibited that holding of oocytes in commonly used transport medium induced changes in the organelles such as rough endoplasmic reticulum, cortical granules, mitochondria and Golgi complexes both in the cumulus cells and those present in the oocytes. The severity of these changes was higher in oocytes transported at 2-4 C than those transported at 35-370 C the effect of which was reflected by the viability test. None of the cleaved oocytes (0/49) in the former while an average of 18.2% (10/55) of the oocytes in the latter developed to morulae. In the second experiment, the oocytes which were submitted to IVM, exhibited ultrastructural changes such as incomplete cumulus expansion, swelling of mitochondria, reduced incidence of cortical granules and accumulation of lipid droplets which were probably the factors affecting the viability of oocytes. In the third experiment, examination of in vitro produced morulae (35/121, 28.9%) revealed the presence of a large number of lipid droplets, vacuoles and numerous mitochondria undergoing the process of degeneration which ultimately may affect the viability of embryos. It was concluded that the ultrastructural changes induced during various stages of in vitro embryo production contribute towards low viability of the in vitro produced embryos.